EARNING MANAGEMENT DETERMINANTS: DOES FAIR VALUE ACCOUNTING MATTER? - Farah Rahmah Putri; Kholilah Kholilah (Fakultas Ekonomi Universitas Negeri Manado, 2023)
This research investigates the impact of fair value accounting, company size, board of commissioners, audit quality, and managerial ownership on earning management. The research was conducted on study 36 companies registered in the financial sector from 2019 to 2021. Purposive sampling is a sampling method to select 36 companies. Multiple linear regression analysis is used in this study's data analysis technique. The findings revealed that fair value accounting, company size, and board of commissioners effected earning management. In contrast to the previous three variables, audit quality and managerial ownership do not affect earning management. Fair value accounting cas be used as a way to check earning management that occurs in companies.